2008
DOI: 10.1007/s11606-008-0859-7
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and Determinants of Inappropriate Antibiotic Use in Injection Drug Users

Abstract: Injection drug users reported potentially dangerous antibiotic use behaviors and described determinants of these behaviors. Outreach and educational interventions to improve antibiotic use should target high-risk populations, such as injection drug users, and consider their distinct antibiotic use behaviors and determinants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…In the clinical settings, inappropriate use accounts for 20%–50% of the antibiotics consumed [ 6 ]. These include the use of antimicrobials for viral infections, the prescription of broad-spectrum antibiotics, non-compliance to a treatment regimen by the patient, and incorrect dosage or duration [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the clinical settings, inappropriate use accounts for 20%–50% of the antibiotics consumed [ 6 ]. These include the use of antimicrobials for viral infections, the prescription of broad-spectrum antibiotics, non-compliance to a treatment regimen by the patient, and incorrect dosage or duration [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Self-treatment or street-treatment procedures are often performed by untrained individuals in nonsterile environments and may increase the risk for further complications. Studies have shown that 27–40% of IDUs had at least once lanced their own abscess, and 16–26% had self-medicated with illegally purchased antibiotics (Binswanger et al, 2000; Starrels, Barg, & Meglay, 2008; Takahashi, Baernstein, Binswanger, Bradley, &Merrill, 2007). The improper use of antibiotics has resulted in a growing medical concern over the development of drug-resistant strains of bacteria; this may be further exasperated by the self-medication of abscesses by IDUs (Levy, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The control of MRSA nosocomial infections is, many times, very difficult because of the presence of this prevalent clone. Additionally, many antibiotics are associated with adverse effects (Starrels et al, 2008).…”
Section: Introductionmentioning
confidence: 99%